Rozwiązanie nierówności
[tex]2x^2-13x+6\leq0\\\\a=2, \ b=-13, \ c=6\\\\\Delta=b^2-4ac\Rightarrow(-13)^2-4\cdot2\cdot6=169-48=121\\\\\sqrt{\Delta}=\sqrt{121}=11\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\Rightarrow\frac{-(-13)-11}{2\cdot2}=\frac{13-11}{4}=\frac{2}{4}=\frac{1}{2}\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\Rightarrow\frac{-(-13)+11}{2\cdot2}=\frac{13+11}{4}=\frac{24}{4}=6\\\\\huge\boxed{x\in\langle\frac{1}{2};6\rangle}[/tex]
a > 0, więc ramiona paraboli są skierowane w górę, kółeczka zamalowane, ponieważ mamy przedział domknięty